Adopcja / opieka zastępcza jako czynnik ryzyka przemocy w rodzinie - Helios, Joanna (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2017)
This article analyzes one of the risk factors for violence against children. Adoption (foster care) has been explicitly identified as such a risk factor due to multiple issues stemming from trauma, relationship disruption, and dissociation, all of which present specific problems. These problems differ from those experienced by biological families, and may therefore cause violence in adoptive and foster families to occur more frequently
Keywords: trauma; dysocjacja; piecza zastępcza; przemoc